Analisa Postur Kerja terhadap Keluhan Musculoskeletal Disorder Operator Hand Stacker Menggunakan Rapid Upper Limb Assessment di PT. AFS, Makassar - Silvana Mohamad; Moh. Ainul Fais (Universitas Katolik Darma Cendika, 2023)
Musculoskeletal Disorders is one of the injuries that workers often experience in material handling activities, namely injuries to muscles, nerves, bones, joints caused by work activities. PT. AFS as a company that focuses on catering services to serve the